A Highly Robust Single-Loop Current Control Scheme for Grid-Connected Inverter With an Improved LCCL Filter Configuration - Pan, Donghua; Ruan, Xinbo; Wang, Xiongfei; Blaabjerg, Frede; Wang, Xuehua; Zhou, Qingfeng (IEEE transactions on power electronics, 2018)
Single-loop current control is an attractive scheme for the LCL-type grid-connected inverter due to its simplicity and low cost. However, conventional single-loop control schemes, which command either the inverter current or the grid current, are subject to the specific resonance frequency regions. The weighted average current control, which splits the filter capacitor into two parts (in form of an LCCL filter) and commands the current flowing between these two parts, is independent of the resonance frequency, but on the other hand, it is limited by the poor sensitivity to the grid impedance variation and weak stability in the grid current. These limitations are comprehensively explained in this paper and then addressed by identifying that the single-loop weighted average current control is equivalent to the dual-loop grid current control with an inherent capacitor current active damping. By tuning the capacitor split proportion as a second degree of freedom, an optimal damping performance that is robust to the grid impedance variation can be naturally achieved using only the inherent damping. Thus, no extra damping is required, and the single-loop structure with only one current sensing turns to be adequate. Moreover, for convenience of practical implementation, an improved LCCL filter configuration is proposed to allow the use of two equal nominal capacitances for the split capacitors. Finally, experiments are performed to verify the effectiveness of the proposed method.